Canadian Jewish Poetry: A Roundtable - Sol , Adam; Koffman, David S.; Barwin, Gary; Greenstein, Michael; Panofsky, Ruth; Richter, Lisa; Robins Sharpe, Emily; Tregebov, Rhea (Canadian Jewish Studies / Études juives canadiennes, 2022)
Is Canadian Jewish Poetry a meaningful category of study? Are there particular traits that differentiate Canadian Jewish poets from poets of other countries, or from writers in other genres? How do contemporary poets confront the looming legacy of Irving Layton, Leonard Cohen, and A.M. Klein? Six prominent poets and scholars conduct a roundtable discussion to articulate recent developments in the field.